Culture and economic growth in selected European countries - Furicová, Veronika; Bič, Josef; Stuchlíková, Zuzana, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The diploma thesis main goal is to show how cultural values are associated with economic growth. The thesis approaches the goal on theoretical and practical grounds. The theoretical part describes three economic growth models and perspectives to culture. The practical part relates to statistical analyses.
Vedoucí práce: Josef Bič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses